Primary cutaneous lymphoma of scalp in a child: a case report - Sri, K. Satya; Lakshmi, A. Bhagya (International Journal of Research in Medical Sciences, 2017)
Cutaneous lymphomas are a heterogenous group of lymphoproliferative disorders with involvement of skin and form a separate group under Non-Hodgkin’s lymphoma. Skin may be involved along with other organs but if the initial manifestation is in the skin, it is referred to as primary cutaneous lymphoma (PCL). One year eight months child brought with a scalp swelling of three months duration. Histopathology revealed a lymphoma and immuno- histochemistry studies were positive for T-cell lymphoma. The case is presented due to the rarity of primary cutaneous lymphoma at the age of one year eight months.